Evaluation of multiple cytokine levels to improve our understanding of protective immune responses against Tuberculosis and to develop novel diagnostic methods - Phalane, Khutso Gemina (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScMedSc)--Stellenbosch University, 2013.